2005
DOI: 10.1002/app.22568
|View full text |Cite
|
Sign up to set email alerts
|

A chelating cellulose adsorbent for the removal of Cu(II) from aqueous solutions

Abstract: Regenerated cellulose wood pulp was grafted with the vinyl monomer glycidyl methacrylate (GMA) using ceric ammonium nitrate as initiator and was further fuctionalised with imidazole to produce a novel adsorbent material, cellulose-g-GMA-imidazole. All cellulose, grafted cellulose and functionalized cellulose grafts were physically and chemically characterized using a number of analytical techniques, including elemental analysis, Fourier transform infrared spectroscopy, thermogravimetric analysis, differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
75
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(75 citation statements)
references
References 39 publications
0
75
0
Order By: Relevance
“…In a typical synthesis of cellulose-g-GMA-imidazole, the same technique was used as described in our previous publication [13]. The regenerated cellulose (Chemcell) originated from Borregaard Industries, Sarpsborg, Norway.…”
Section: Methodsmentioning
confidence: 99%
“…In a typical synthesis of cellulose-g-GMA-imidazole, the same technique was used as described in our previous publication [13]. The regenerated cellulose (Chemcell) originated from Borregaard Industries, Sarpsborg, Norway.…”
Section: Methodsmentioning
confidence: 99%
“…Indirect modification by graft copolymerization is one of the alternative procedures that provided high efficient cellulose-based metal adsorbent 5) . The grafted cellulose with various functionality for heavy metal adsorption have been reported such as acrylic acid 10) , acrylamide 11) , acrylnonitrile 12) 13) and glycidyl methacrylate 14) . Acrylic acid and acrylamide contain carboxyl (-COOH) and amide (-CONH2) groups.…”
Section: Introductionmentioning
confidence: 99%
“…Copper (Cu 2+ ) is one of the most widespread heavy metal contaminants in the environment (O'Connell et al, 2006) and one of the most toxic heavy metals to living organisms. High Cu 2+ levels in drinking water can cause vomiting, abdominal pain, nausea and diarrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Many natural materials such as peat, sawdust, peanut and hazelnut shells have been studied for treating metal-contaminated wastewater (Brown et al, 2000). The results of these studies showed that Cu 2+ sorption using natural materials is effective, efficient, and economical in comparison to traditional methods for water decontamination (O'Connell et al, 2006) because biomass materials are abundant and readily available at a very low cost. Cadmium (Cd 2+ ) sorption to biomass depends on the initial pH of the reaction mixture because pH dramatically influences surface activities of sorbents (Horsfall and Spiff, 2004 .…”
Section: Introductionmentioning
confidence: 99%